Obesity-associated alterations in cardiac connexin-43 and PKC signaling are attenuated by melatonin and omega-3 fatty acids in female rats - Egan Benova, Tamara; Viczenczova, Csilla; Szeiffova Bacova, Barbara; Knezl, Vladimir; Dosenko, Victor; Rauchova, Hana; Zeman, Michal; Reiter, Russel J; Tribulova, Narcis (Molecular and cellular biochemistry, 2019)
We aimed to explore whether specific high-sucrose intake in older female rats affects myocardial electrical coupling protein, connexin-43 (Cx43), protein kinase C (PKC) signaling, miR-1 and miR-30a expression, and susceptibility of the heart to malignant arrhythmias. Possible benefit of the supplementation with melatonin (40 µg/ml/day) and omega-3 polyunsaturated fatty acids (Omacor, 25 g/kg of rat chow) was examined as well. Results have shown that 8 weeks lasting intake of 30% sucrose solution increased serum cholesterol, triglycerides, body weight, heart weight, and retroperitoneal adipose tissues. It was accompanied by downregulation of cardiac Cx43 and PKCε signaling along with an upregulation of myocardial PKCδ and miR-30a rendering the heart prone to ventricular arrhythmias. There was a clear benefit of melatonin or omega-3 PUFA supplementation due to their antiarrhythmic effects associated with the attenuation of myocardial Cx43, PKC, and miR-30a abnormalities as well as adiposity. The potential impact of these findings may be considerable, and suggests that high-sucrose intake impairs myocardial signaling mediated by Cx43 and PKC contributing to increased susceptibility of the older obese female rat hearts to malignant arrhythmias.
Keywords: Animals; Heart; Fatty Acids, Omega-3; konzumní sacharóza; antiarytmika; Female; Rats, Wistar; Ventricular fibrillation; Melatonin; ženské pohlaví; Cardiac connexin-43; Obesity; srdce; Adiposity; signální transdukce; Dietary Sucrose; Arrhythmias, Cardiac; Signal Transduction; proteinkinasa C-epsilon; omega-3 mastné kyseliny; obezita; Connexin 43; melatonin; mikro RNA; Sucrose diet; krysa rodu Rattus; konexin 43; Omega-3 PUFA; MicroRNAs; zvířata; Protein Kinase C-epsilon; Anti-Arrhythmia Agents; Myocardium; myokard; Protein Kinase C-delta; Female rats; Rats; proteinkinasa C-delta; srdeční arytmie; potkani Wistar